IMPLEMENTASI METODE UMMI DALAM MENINGKATKAN KEMAMPUAN HAFALAN DAN TERJEMAH AL-QUR’AN (Studi Kasus di MI Kresna Mlilir Dolopo Madiun) - Azizah, Channa Nur; Iman, Nurul; Nuraini (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to describe the implementation of the Ummi method in improving students’ memorization and translation skills of the Qur’an at MI Kresna Mlilir Dolopo Madiun. This research employed a qualitative approach with a case study design. The subjects consisted of the principal, Qur’an–Hadith teachers, and students from grades IV to VI. Data were collected through observation, in-depth interviews, and documentation. The data analysis used Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The results show that the implementation of the Ummi method was carried out through several stages: tashih (correction of recitation), talaqqi (direct learning), murojaah (repetition), and tasmi’ (listening test). The method effectively enhanced students’ Qur’anic memorization abilities and improved their understanding of verse meanings through simple translation activities. Supporting factors include certified teachers, strong institutional support, and parental involvement in home practice, while inhibiting factors involve differences in students’ abilities and limited learning time. Overall, the Ummi method proved effective in increasing students’ Qur’an memorization and translation skills at MI Kresna Mlilir Dolopo Madiun